2007
DOI: 10.1038/emm.2007.64
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of γ ray-induced apoptosis by stimulatory heterotrimeric GTP binding protein involves Bcl-xL down-regulation in SH-SY5Y human neuroblastoma cells

Abstract: Heterotrimeric GTP-binding proteins (G proteins) transduce extracellular signals into intracellular signals by activating effector molecules including adenylate cyclases that catalyze cAMP formation, and thus regulate various cellular responses such as metabolism, proliferation, and apoptosis. cAMP signaling pathways have been reported to protect cells from ionizing radiation-induced apoptosis, but however, the protective mechanism is not clear. Therefore, this study aimed to investigate the signaling molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…In many cases, the radiation-induced cell damage results in apoptosis [31]. In our present study, low GEN dosage exerted its protective action on L-02 cell viability, as evidenced by decreasing the apoptosis rate induced by X-ray irradiation.…”
Section: Discussionmentioning
confidence: 92%
“…In many cases, the radiation-induced cell damage results in apoptosis [31]. In our present study, low GEN dosage exerted its protective action on L-02 cell viability, as evidenced by decreasing the apoptosis rate induced by X-ray irradiation.…”
Section: Discussionmentioning
confidence: 92%
“…21 The underlying mechanism was only recently elucidated, showing that Gs inhibits radiation-induced apoptosis by restraining downregulation of Bcl-xl. 39 The cAMP-dependent protein kinase signaling pathway also seems to be involved in the acquisition of cisplatin resistance after irradiation. 40 It has been recently shown that the CC genotype of T393C polymorphism shows the lowest GNAS1 expression.…”
Section: H Alakus Et Almentioning
confidence: 99%
“…Furthermore, we showed that PGE2 augmented gamma ray-induced apoptosis of H1299 cells via Gαs-coupled receptor, as stimulation of beta-adrenergic receptor induced cell death of thymocytes (Gu et al, 2000). However, Gαs protein was reported to inhibit radiation-or hydrogen peroxide-induced apoptosis of SH-SY5Y human neuroblastoma cells (Kim et al, 2007(Kim et al, , 2008. Inhibitory G proteins were found to antagonize the anti-apoptotic effect of Gαs in hydrogen peroxide-treated SH-SY5Y human neuroblastoma cells (Kim et al, 2008) and also to inhibit hydrogen peroxide-induced apoptosis by up-regulation of Bcl-2 via NF-κB in H1299 human lung cancer cells (Seo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of proteins was analyzed by western blotting using specific antibodies as described previously (Kim et al, 2007). Antibodies against β-actin and Bcl-2 were purchased from Santa Cruz Biotechnology (Santa Cruz, CA), antibodies against PARP, cleaved PARP, cleaved caspase-3, Bax, Bcl-XL, and Bak were obtained from Cell Signaling Technology (Beverly, MA).…”
Section: Immunoblot Analysismentioning
confidence: 99%